Viability of rat spermatogenic cells in vitro is facilitated by their coculture with Sertoli cells in serum-free hormone-supplemented medium. - Tres, L L (1983)
Spermatogenic cells from 20- to 35-day-old rats were grown in vitro in the presence of Sertoli cells maintained in serum-free hormone/growth factor-supplemented medium and alternating high/low concentrations of follicle-stimulating hormone in the medium. In cell reaggregation experiments, spermatogenic cells reassociate with Sertoli cells but not with peritubular cells or cell-free substrate. Autoradiographic experiments using [3H]thymidine as a labeled precursor for DNA synthesis show that spermatogonia and preleptotene spermatocytes, connected by cytoplasmic bridges, have a synchronous S phase. [3H]Thymidine-labeled preleptotene spermatocytes progress until later stages of meiotic prophase. Time-lapse cinematographic studies of Sertoli/spermatogenic cell cocultures show three major movement patterns. While Sertoli cell cytoplasmic processes between adjacent cells display tensional forces, spermatogonia are engaged in oscillatory cell movements different from the nuclear rotation observed in meiotic prophase spermatocytes. Results of this study show that the proliferation of premeiotic cells and the differentiation of meiotic prophase cells do occur in vitro in association with Sertoli cells maintained in a medium that allows differentiated cell functions.